Integrated stratigraphy of the Priabonian (upper Eocene) Urtsadzor section, Armenia - Cotton, Laura; Zakrevskaya, Elena Y.; Boon, Annique van der; Asatryan, Gayane; Hayrapetyan, Flora; Israelyan, Arsen; Krijgsman, Wouts; Less, Gyorgy; Monechi, Simonetta; PAPAZZONI, Cesare Andrea; Pearson, Paul N.; Razumovskiy, Anatoli; et al. (Newsletters on Stratigraphy, 2017)
The transition from the Bartonian to the Priabonian, as traditionally understood, has long been associated with a series of extinctions and originations in several microfossil groups. The planktonic forami- nifer genus Morozovelloides and large species of Acarinina suffered a rapid global extinction, as did many radiolarians. Calcareous nannofossils show several assemblage changes including the acme beginning of Cri- brocentrum erbae and the lowest and highest occurrences of Chiasmolithus oamaruensis and C. grandis re- spectively. In shallow water environments, larger foraminifera also show an extinction among large species of Nummulites, as well as the first occurrences of the stratigraphically important genus Spiroclypeus. Howe- ver, the correlation between shallow and deep water records remains uncertain, as do the mechanisms driving these biotic events. Here we present the results of a new integrated stratigraphical study (calcareous nanno- fossils, planktonic foraminifera, larger benthic foraminifera, and low-resolution magnetostratigraphy) of the Urtsadzor section in south-western Armenia which appears to be continuous through this interval. The Urt- sadzor section consists of calcareous siltstones rich in micro- and nannofossils, with interbedded limestones containing abundant larger benthic foraminifera. Our new data enable us to correlate larger foraminiferal events with global plankton biostratigraphy, in a section outside of southwest Europe where most previous correlations have been based. At Urtsadzor, the large Nummulites species of N. millecaput-group are present throughout the whole section but decrease in abundance toward the top. The first occurrence of Spiroclypeus, also occurs in the upper part of the section, marking the SBZ 18/19 boundary. These events are associated with the phylogenetic development of the Nummulites fabianii and Heterostegina reticulata lineages. Howe- ver, the calcareous plankton biostratigraphy indicates the section is well within the Priabonian; within plank-tonic ...